2022
DOI: 10.3389/fphys.2022.990142
|View full text |Cite
|
Sign up to set email alerts
|

The elite judo female athlete’s heart

Abstract: Purpose: There is a paucity of data on physiological heart adaptation in elite-level judo female athletes. This study aimed to assess left ventricular morphology and function in highly trained elite female judokas.Methods: The study prospectively included 18 females aged 23.5 ± 2.25 years, nine elite level judokas, and nine healthy non-athlete volunteers. All participants underwent a medical examination, electrocardiogram, and transthoracic 2D echocardiogram. Left ventricular diastolic and systolic diameters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…As expected, significantly greater LV changes were observed in male compared to female athletes. The literature has already established that judokas, regardless of gender, have a significantly higher RWT and greater left ventricular mass than non-athletes of the same gender 17 , however the cardiac remodeling is complex and depends on various factors 18 . The results obtained are in line with research conducted to date, which indicate that gender is a significant factor that has an important influence on the change of heart geometry in athletes 19 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, significantly greater LV changes were observed in male compared to female athletes. The literature has already established that judokas, regardless of gender, have a significantly higher RWT and greater left ventricular mass than non-athletes of the same gender 17 , however the cardiac remodeling is complex and depends on various factors 18 . The results obtained are in line with research conducted to date, which indicate that gender is a significant factor that has an important influence on the change of heart geometry in athletes 19 20 .…”
Section: Discussionmentioning
confidence: 99%
“…There is currently little evidence regarding cardiac adaptation to resistance training in women. However, one study suggests that elite and highly trained female judokas show significant changes in the morphology of the LV 18 . A cross-sectional report revealed that 24 female weightlifters demonstrated concentric enlargement of the LV 27 .…”
Section: Discussionmentioning
confidence: 99%